2018
DOI: 10.1002/cbic.201800551
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in Vitro Characterization of Trehalose‐Based Inhibitors of Mycobacterial Trehalose 6‐Phosphate Phosphatases

Abstract: α,α′‐Trehalose plays roles in the synthesis of several cell wall components involved in pathogenic mycobacteria virulence. Its absence in mammalian biochemistry makes trehalose‐related biochemical processes potential targets for chemotherapy. The trehalose 6‐phosphate synthase (TPS)/trehalose 6‐phosphate phosphatase (TPP) pathway, also known as the OtsA/OtsB2 pathway, is the major pathway involved in the production of trehalose in Mycobacterium tuberculosis (Mtb). In addition, TPP is essential for Mtb survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Recently, there has been some exciting work to devise inhibitors specific for OtsB of Mycobacteria which are based on substrate analogs. These results showed that 6- N -phosphonamide 6 (TNP) exhibited the highest inhibitory activity toward the M. tuberculosis OtsB [ 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been some exciting work to devise inhibitors specific for OtsB of Mycobacteria which are based on substrate analogs. These results showed that 6- N -phosphonamide 6 (TNP) exhibited the highest inhibitory activity toward the M. tuberculosis OtsB [ 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose (-d-glucopyranosyl--d-glucopyranoside) is an essential nonreducing disaccharide used in bacteria, fungi, parasitic nematodes, insects, and plants, but it is not used in vertebrates (1)(2)(3)(4)(5). It has several functions including as a source of carbon and energy, as a signaling molecule to control metabolic pathways, and also to protect cellular membranes and proteins from denaturation or inactivation caused by a variety of stress conditions including desiccation, heat, dehydration, cold, and oxidation (3,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…4f As one might expect this correlation of the 2 J PH2 with phosphorus stereochemistry does not seem to be applicable to our 2deoxy compounds, in which the 2 J PH2 and 2 J PH2 are in general very similar and considerably higher (ca. [16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%